Waiting for snow - Arnold, Marsha Diane (Houghton Mifflin Harcourt, 2016)
"Badger cannot wait one more minute for it to snow. When his friend Hedgehog explains that everything comes in its time, Badger is unconvinced and impatient as ever. But Badger's friends have a few tricks up their sleeves to try and get the snow's attention and distract their pal in the meantime"...